(untitled) - Gregory, Hamilton (Boston, 2005)
Public Speaking for College and Career combines a wealth of business oriented examples, and patient step by step instruction to writing and developing a speech, with an open accessible design. Thus the book is ideal for schools where a practical, non-intimidating approach is essential for student learning. The new edition covers more on the impact of new technologies, from doing research on the internet to gleaning the essential from the cornucopia of information available to today's students. New group activities encourage the cooperation demanded by employers in the business world.
Keywords: Public speaking,Nói chuyện trước công chúng